Continuity of Care Of Klinik & RB Delta Mutiara - Risma Wanda Wardani; Putri Ancila Citra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Continuity of Care (CoC) is a health service approach that emphasizes continuity of care through ongoing relationships, coordinated management, and integrated information between health workers and clients. This study aims to describe the application of Continuity of Care in midwifery care at the Delta Mutiara Clinic & Maternity Home (RB). The research method used is a case study with a subject of a 30-year-old pregnant woman (G2P1A0) who received continuous midwifery care starting from pregnancy, childbirth, postpartum, newborn care, to family planning. Data collection was carried out through observation, interviews, and documentation of midwifery care according to midwifery practice standards. The results of the study indicate that the application of Continuity of Care is able to provide comprehensive and continuous midwifery care, characterized by stable conditions of mothers and babies, no complications found, and increased understanding and independence of mothers in caring for themselves and their babies. The conclusion of this study is that the Continuity of Care model is effective in improving the quality of midwifery services and supporting the achievement of optimal maternal and infant health.